Application of data mining technologies for analysis of Šiauliai university’s young computer users’ school - Turskienė, Sigita; Kulvietis, Genadijus; Burbaitė, Renata (Lietuvos matematikos rinkinys, 2003)
The paper analyses possibilities of using data mining technologies for investigation of activity of Šiauliai university’s young computer users’ school. The application’s domains, principal stages of mining model’s creation are analyzed. Data mining models young computer users’ school was made by using WIZWHY, XPERTRULE MINER, STATGRAPHICS, INTELLIGENT MINER SYSTEMS. The basic tendencies of young computer users’ school activity are presented and the recommendations for school’s activity improvement are formulated.